Cultural and Environmental Concepts in Russian, English, and Arabic: The Impact of Conceptual Differences on Translation: Культурные и Экологические Концепты в Русском, Английском и Арабском Языках: Влияние Концептуальных Различий на Перевод (Journal of the College of Languages (JCL), 2025)
The problem of differences in conceptual frameworks and systems between languages is one of the main problems in translation theory and practice. Given its importance, this problem is chosen as the subject of this study. This paper aims to identify ways to analyse it and develop effective solutions that help overcome the difficulties translators face in the translation process. To illustrate the problem under study, specific examples were chosen to help clarify the research idea and provide answers to key aspects of the research topic. One of the main topics addressed in the article is the concept. It is a general mental structure that includes a system of concepts that reflect reality. It is linked to surrounding objects and phenomena through the symbols they represent. Therefore, a concept can be defined as a system consisting of moral and cultural ideas symbolically linked to a specific reality and expressed in linguistic forms. One of the most important conclusions of the study is the necessity for the translator to be familiar with the cultural and linguistic environment of both the source and target languages. Particular attention should be paid to vocabulary related to the environmental and cultural reality of both linguistic systems. This allows for the accurate transmission of the meaning of the text and makes it more comprehensible to native speakers of the target language.АннотацияПроблема различий в концептуальных основах и системах между языками является одной из ключевых в теории и практике перевода. В силу её актуальности данная проблема была выбрана в качестве предмета исследования. Целью работы стало выявление путей её диагностики и разработка эффективных решений, способствующих преодолению трудностей, с которыми сталкивается переводчик в процессе перевода.Для иллюстрации исследуемой проблемы были подобраны конкретные примеры, позволяющие уточнить суть вопроса и найти ответы на ключевые аспекты темы.Одним из ключевых понятий, рассматриваемых в статье, является концепт, который представляет собой обобщённую ментальную структуру, включающую в себя систему понятий, отражающих действительность. Он связан с объектами и явлениями окружающего мира посредством символов, которые их обозначают. Таким образом, концепт можно определить как систему, состоящую из моральных и культурных идей, символически соотносимых с конкретной реальностью и находящих выражение в языковых формах.Одним из наиболее значимых выводов исследования стала необходимость глубокого знакомства переводчика с культурной и языковой средой как исходного, так и целевого языков. Особое внимание следует уделять лексике, связанной с экологическими и культурными реалиями обеих языковых систем. Это позволяет достичь точности передачи смысла текста и делает его более понятным для носителя языка перевода.